1996
DOI: 10.1002/(sici)1097-4636(199602)30:2<261::aid-jbm17>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Bone-bonding behavior of plasma-sprayed coatings of BioglassR, AW-glass ceramic, and tricalcium phosphate on titanium alloy

Abstract: The bone-bonding behavior of three kinds of bioactive ceramics coated on titanium alloy by the plasma-spray technique was investigated. Titanium alloy (Ti-6A1-4V) coated with BioglassR (45S5), apatite-wollastonite containing glass ceramic (AW), or beta-tricalcium phosphate (TCP) was prepared, and rectangular specimens were implanted into the tibial bones of mature male rabbits, which were sacrificed 8 or 24 weeks after implantation. The tibiae containing the implants were dissected out and subjected to detachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 20 publications
0
63
0
1
Order By: Relevance
“…Apatite formation on the surface of the material is considered a prerequisite for direct bone-bonding. Details of the mechanism underling apatite formation on the surface of alkali-and heat-treated titanium metals have been described by Kim et al 7) Osteogenic cells may attach to the surface of alkali-and heat-treated titanium alloy implant themselves or to the apatite formed on the surface, and this may enhance growth and differentiation [27][28][29][30][31] . Thus, the gap initially created between the bone and the implant following the implantation procedure may be filled with new bone faster with alkali-and heat-treated implants than with untreated implants.…”
Section: Discussionmentioning
confidence: 99%
“…Apatite formation on the surface of the material is considered a prerequisite for direct bone-bonding. Details of the mechanism underling apatite formation on the surface of alkali-and heat-treated titanium metals have been described by Kim et al 7) Osteogenic cells may attach to the surface of alkali-and heat-treated titanium alloy implant themselves or to the apatite formed on the surface, and this may enhance growth and differentiation [27][28][29][30][31] . Thus, the gap initially created between the bone and the implant following the implantation procedure may be filled with new bone faster with alkali-and heat-treated implants than with untreated implants.…”
Section: Discussionmentioning
confidence: 99%
“…A hook was constructed on the center of each disc, using a 0.76 mm-diameter piece of titanium wire that was bent into a loop and welded in place. The bone-contacting surfaces of the implants were coated with 伪-TCP using the plasma spray method [2][3][4][5][6][7][8][9] . The HA coating was created by hydrothermally processing the 伪-TCP-coated surface (procedure performed by Advance, Tokyo, Japan).…”
Section: Preparation Of Implantsmentioning
confidence: 99%
“…Several groups have attempted to coat metallic implants with bioactive glasses using enameling, rapid immersion in molten glass, or plasma-spraying techniques. [10][11][12][13] Although some coatings with excellent in vitro behavior have been obtained, most of the glass coatings are marred by cracking and poor reliability at the glass/metal interface. 10,12 In many cases glass/metal reactions lead to the formation of brittle interfacial layers and gas bubbles in the coating.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Although some coatings with excellent in vitro behavior have been obtained, most of the glass coatings are marred by cracking and poor reliability at the glass/metal interface. 10,12 In many cases glass/metal reactions lead to the formation of brittle interfacial layers and gas bubbles in the coating. 14,15 It has been suggested that future progress in biomaterials must include the development of coatings with programmed dissolution of multilayer surfaces.…”
Section: Introductionmentioning
confidence: 99%